Dantrakshanam: An Ancient Wisdom For Modern Dental Care- An In Vivo Clinical Study (International Journal of Environmental Sciences, 2025)
CharakSamhita advocated the Tridosha theory of disease which categorizes human beings into Vata, Pitta, and Kapha groups based on the body constitutional type. According to this theory disease is explained as disturbance in the equilibrium of the three humors. There is a strong association of Pitta dosha and oral health. The present clinical study aims to evaluate and compare the Salivary pH , strep mutans count and DMFT among children with Pitta Dosha. A total of 30 subjects aged 8-12 years visiting the OPD of Ayurvedic Hospital were included in the clinical study. Only those children with predominant Pitta Dosha were included in the study. Strep mutans count, salivary pH and DMFT score of each patient was checked at baseline and after three months Statistical analysis was done to find the association between Pitta Dosha and dental caries. It was found that mean DMFT score was high among all the subjects. There was a statistically significant reduction found in strep mutans count and salivary pH in the subjects who received ayurvedic treatment for their Pitta dosha. The results confirmed that modification of Pitta prakriti type in the patients can reduce the chances of having dental caries and also can influence individuals’ susceptibility to oral disorders.